Auditoría de cumplimiento de las obligaciones tributarias y su incidencia en el rendimiento financiero de la empresa “Agroservicios ubilla”, cantón Buena Fe, año 2013 - Muñiz Saltos, María Mercedes (2015)
At present the taxes have turned into one of the most significant titles of the General Budget of the State, for such a reason the current Government is implementing new strategies for an efficient collection; in which one tries to spread a tributary culture to all the Ecuadorians and resident foreigners, based on a just support that he contributes to the development and the economy of the country; this project was based on the detailed investigation of the arrears of tax that has the company in study which are: Annex of Buys and Retentions in the Source for Other concepts, Annex of Relation of Dependence, Declaration of Retentions in the Source and the Monthly Declaration of Value-added tax; by means of the achievement of an Audit of Fulfillment, applying different methods and skills for the development of the same one. This work investigative shows the enterprise description, its countable procedures, as well as also the analysis of the arrears of tax. The fundamental intention is to verify that the impositions mentioned previously are fulfilled in accordance with the regulations and tributary laws in the period 2013, by means of the evaluation of the Internal Control and the conciliations of the declarations carried out to the Services of Internal Revenues (SRI); the Audit of Fulfillment was carried out in conformity with the International Norms of Audit (NIA'S), Internal Control as the system C.O.S.O. I; and the Tributary Laws corresponding to the tax year 2013.